Synergy of Tri Center of Education in Early Childhood Character Building in Scavenger Village Environment - Listyaningrum, R. Anggia; Dayati, Umi; Sugeng Desyanty, Ellyn; Arina Rahma, Rezka (Universitas Negeri Padang, 2023)
Children's character building is one of the tasks of parents and families, but it will be more effective if done in collaboration with school institutions and the community. This is because these three parties are the Tri Center of Education. The success of education will depend on how the synergy of the three parties in working together to educate children. This also applies to the formation of children's character. The purpose of this study is to obtain the results of an analysis of the synergy of the Tri Center of Education in shaping children's character, especially in the scavenger village environment. This research method uses a qualitative method of case study type. Data collection was conducted in Scavenger Village using interview, observation, and document study techniques. This was done to examine how the synergy of the Tri Center of Education in the middle to lower economic level, which is not a conducive environment to educate their children. The results showed that in Scavenger Village, the synergy of the Tri Center of Education has been built in early childhood character building. Parents at home actively provide stimulus in the form of habituation, teachers at PAUD schools teach character values, and are supported by the community who informally form an environment that familiarizes children to respect each other.